EVALUATION OF ANTI-ALZHEIMER ACTIVITY OF ETHANOLIC AND METHANOLIC EXTRACTS OF POLYGONUM GLABRUM AGAINST ALUMINUM CHLORIDE-INDUCED ALZHEIMER’S IN EXPERIMENTAL RATS - Y, SUNEESHA; KUMAR T, VINAY (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The current study aimed at the investigation of the effectiveness of ethanolic and methanolic extract of Polygonum glabrum in aluminum chloride-induced Alzheimer’s disease in experimental rats. Methods: The behavioral parameters evaluated by following methods such as Morris water maze test, radial arm maze test, and active avoidance test. Biochemical parameters were also estimated such as acetylcholine and acetylcholine esterase. Results: Polygonum glabrum extract was instituted to be neuroprotective against AlCl3-induced toxicity. Enhanced learning and memory were allied to the ingestion of extract in rats. Al overload, acetylcholinesterase enzyme hyperactivity is responsible for Alzheimer’s disease which is neutralized or reduced with treatment of extract, which might be due to the synergistic action of its active constituents. Ethanolic extract was shown slightly higher efficacy as compared to methanolic extract. Conclusion: Based on these current findings, it is suggested that lowering Aβ is an unproven strategy, and it may be time to refocus on other targets for the treatment of this disease, including pathological forms of tau.